Prevention Method for Stack Buffer Overflow Attack in TA Command Calls in OP-TEE - Shiba, Kaito; Kuzuno, Hiroki; Yamauchi, Toshihiro (International Symposium on Computing and Networking Workshops (Online), 2023)
TEE systems provide normal world and secure world. It is impossible to gain access to the secure world directly from the normal world. However, vulnerabilities in the secure world can cause attacks to compromise the secure world. In this study, we investigate the security features applied to trusted applications (TA) in OP-TEE and clarify the lack of protection against stack buffer overflow in TA command calls. We also propose a method for preventing attacks that exploit stack buffer overflows in TA command calls. In addition, the experimental results show that attacks on the vulnerable TAs can be prevented with the proposed method and the overhead can be evaluated.